Technologies in the creation of images in classrooms. A case study of three public schools : Mediación crítica en Arte y Cultura Visual - Alonso-Sanz, Amparo; Lifante, Yolanda; Rueda, Paloma (Pulso. Revista de educación, 2018)
This research forms part of a project entitled “A study of the aesthetic quality of three Valencian schools” that delves into the techniques and technologies used in the creation of images at schools, as a variable of educational quality. The research methodology is plural, combining artistic, qualitative and quantitative methods. The data collection consists in photographing the images that are displayed on the walls of 27 classrooms at 3 schools. The photographs are analysed qualitatively according to their technology. Through image-based research, they are classified according to their production processes: mechanical, manual, or mixed technology. The results are presented through a mixed instrument that shows quantitative, qualitative and aesthetic values of this visual heritage, thanks to the numerous photographic series resembling graphs, which are the visual testimony of each classroom. After the typologies of the displayed images at the schools have been documented, it is observed that mechanical technologies are used primarily to create school images and that there is an overuse of clipart that is not adapted to the idiosyncrasy of each educational community. Finally, alternatives are proposed in order to improve the school’s aesthetical quality.
Keywords: Aesthetic quality; Visual culture; Mixed methods; School; Technology